Solenopsis mothiana (Campanulaceae), a new species from Sicily - Brullo, Cristian; Brullo, Salvatore; Del Galdo, Gianpietro Giusso (Phytotaxa, 2013)
Solenopsis mothiana (Campanulaceae) is described and illustrated as a new species from Sicily. A full description, diagnostic characters, ecological requirements, conservation status, SEM, and seed micro-morphology of this narrow endemic are provided. It is taxonomically well differentiated from the other hitherto known species of the genus, which are restricted to the Mediterranean and Macaronesian regions. Its taxonomic isolation is also confirmed by a phenetic analysis based on morphological features. The new species mainly differs from the other taxa of Solenopsis in having sub-caulescent habit, very short and branched stems, leaves arranged in a basal rosette and cauline, and a very small white corolla with sub-connivent lips. From an ecological viewpoint, it behaves as a hygrophyte linked to temporary submerged depressions close to coastal salt marshes.